Hubungan Antara Tingkat Kepercayaan Diri dengan Prestasi Belajar pada Siswa MTs di Demak - Rifkya Maulana; Wigyo Susanto (Journal of Health, Medical, and Psychological Studies, 2026)
This study aimed to examine the relationship between self-confidence and academic achievement among students of MTs in Demak. The research employed an empirical quantitative approach with a cross-sectional design involving 114 students selected through probability sampling using the Slovin formula. Self-confidence was measured using a validated Likert-scale questionnaire with high reliability (Cronbach’s Alpha = 0.949), while academic achievement was obtained from documented report card averages. Univariate analysis indicated that most students had moderate levels of self-confidence and fairly good academic achievement. Bivariate analysis using Spearman Rho revealed a very strong positive correlation between self-confidence and academic achievement (r = 0.843; p < 0.05). The findings demonstrate that higher levels of self-confidence are associated with better academic outcomes. The results support psychological theories emphasizing the role of internal affective factors in learning performance and highlight the importance of strengthening students’ self-confidence to improve educational quality at the secondary Islamic school level.